EFEKTIVITAS KEPEKATAN LARUTAN SODIUM HYPOCHLORITE TERHADAP BIAKAN KUMAN STAPHYLOCOCCUS AUREUS - Effendi, Fajar Ivan; Ernawan, Rieva; Utomo, Pamudji; Mariyanto, Ismail; Santoso, Asep (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2021)
Abstract Musculoskeletal infections have complex complications, making them a challenge. Most countries have experienced Staphylococcus aureus resistance to methicillin by 25% and some even over 50%. Dakin solution (0.050% to 0.025%) can be used as irrigation, cleansing, and used on moist gauze for the management or prevention of skin or tissue infections. This study aims to determine the lowest concentration level of Dakin solution / sodium hypochlorite which is the safest and most effective in the culture of Staphilococcus aureus. This research is an analytical experimental research, with the concept of comparing the Staphylococcus aureus ATCC 25923 germ cultures which are treated in the form of giving dakin solution / sodium hypochlorite 0.050%, 0.025%, 0.0125% and control using 0.9% NaCl. Observation of the effectiveness is done by measuring the formed inhibition zone. The concentration of 0.025% gives a fairly good disinfectant effect with moderate inhibition power, the concentration of 0.050% gives a good disinfectant effect with a strong inhibitory power while the concentration of 0.0125% does not have a disinfectant effect, this is the same as the 0.9% NaCl control solution. The zone of inhibition in the staphylococcus aureus bacteria culture ATCC 25923 at concentrations of 0.025% and 0.050% still gave a stable effect until evaluation within 2x24 hours (48 hours). Keywords : Dakin solution, Sodium hypoclorite, resistor zone, Staphylococcus aureus.